Advances in clinical diagnosis and treatment of gastroenteropancreatic neuroendocrine tumor G3 - GAO Heli, XU Jin, YU Xianjun (Zhongguo aizheng zazhi, 2021)
Neuroendocrine neoplasms are rare and heterogenous, with low incidence, which can occur in multiple organs of the body. Gastroenteropancreatic neuroendocrine neoplasms have the highest incidence in China. 2017 version World Health Organization (WHO) classification of gastroenteropancreatic neuroendocrine neoplasms put forward the concept of well- differentiated neuroendocrine tumors (NET) G3. The related research has started to increase. This article reviewed the latest advances in clinical diagnosis and treatment of well-differentiated gastroenteropancreatic NET G3.